Evaluation of «ICEYE» space system application efficiency - M. V. Pavlov; M. P. Teremov (Космические аппараты и технологии, 2024)
The purpose of this paper is to evaluate the application efficiency of the “ICEYE” space system using the developed software-implemented simulation model of Earth remote sensing space systems application. The article analyzes the reasons for the rapid expansion of the orbital constellation of the ICEYE space system based on small spacecraft equipped with synthetic aperture radar and its composition. The application efficiency of the Earth remote sensing space system was evaluated on the basis of a software-implemented simulation model. The initial data for modeling were the orbital parameters of the ICEYE spacecrafts and the corresponding angles of view for different imaging modes, as well as the coordinates of ground receiving stations. As a result of modeling, average values of periodicity of observation of the Earth surface areas and efficiency of radar information delivery to consumers were obtained. Frequency of observation of the Earth surface areas is presented for different imaging modes as a function of geodetic latitude. And the efficiency of radar information delivery to consumers when transmitting information via ground receiving stations of remote sensing data of «Kongsberg Satellite Service» company is presented in the form of a heat map.